Diversity in Medical Education: A Review Article - Mahmood Enad Al-Majmaie, Imad; I Alezzi, Jalil; Mohammed Batarfi , Ali (Diyala Journal of Medicine, 2023)
Background: Medical education and training differ substantially throughout the world. Several teaching approaches have been used in medical education, which is a dynamic area of educational research. Objective: To assess the process of medical education, its development, and related obstacles to having proper and enhanced medical education, as well as improvement in various aspects related to medical education. Conclusion: Medical educational programs play a critical role in preparing individuals for careers in medicine. These programs offer an organized curriculum that comprises preclinical & clinical education, electives and specialized training, professional development, and research.